2023
DOI: 10.23919/cje.2022.00.040
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Color Classification in TCM with Noisy Labels via Confident-Learning-Assisted Knowledge Distillation

Abstract: Tongue color is an important tongue diagnostic index for traditional Chinese medicine (TCM). Due to the individual experience of TCM experts as well as ambiguous boundaries among the tongue color categories, there often exist noisy labels in annotated samples. Deep neural networks trained with the noisy labeled samples often have poor generalization capability because they easily overfit on noisy labels. A novel framework named confident-learning-assisted knowledge distillation (CLA-KD) is proposed for tongue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Before synthesizing the corresponding stereo pairs from new viewpoints using forward warping, we take care to solve the problems associated with occlusions and artefacts. Recent studies have shown that pre-training a significant amount of data with noisy labels can enhance the performance of image classification [21][22][23][24]. Inspired by this, we applied a similar approach to train a stereo matching network.…”
Section: Introductionmentioning
confidence: 99%
“…Before synthesizing the corresponding stereo pairs from new viewpoints using forward warping, we take care to solve the problems associated with occlusions and artefacts. Recent studies have shown that pre-training a significant amount of data with noisy labels can enhance the performance of image classification [21][22][23][24]. Inspired by this, we applied a similar approach to train a stereo matching network.…”
Section: Introductionmentioning
confidence: 99%